Improving aerobic capacity (IAAF @-Letter for CECS Level II Coaches, 2003)
One important aim of training for events of 400 m and over is to build up aerobic capacity. This involves an increase in the number and volume of mitochondria, an increase in the concentration of enzymes within the mitochondria, an increase in the capillary density and a conversion of some fast-twitch glycolytic (FTb) fibers into fast-twitch oxidative (FTa) fibers. Various distances are run in training for the middle- and long-distance athletes. What these distances are doing for the limiting processes is explained below.